A clinical pharmacist-led integrated approach for evaluation of medication errors among medical intensive care unit patients. Issue 1 (9th March 2021) - Aghili, Mina; Neelathahalli Kasturirangan, Meera
ABSTRACT: Aim: Medication errors jeopardize the safety of critically ill patients. Using only one method for the detection of medication errors may not reflect an existing picture of patient safety accurately. Therefore, we designed a clinical pharmacist-led integrated approach to evaluate incidence rate, type, and severity of medication errors and preventable adverse drug events (ADEs) and to assess the impact of the implementation of interventions recommended by the clinical pharmacist. Methods: A prospective study was conducted from November 2017 to January 2019 in the medical ICU. The clinical pharmacist performed a combination of medication error detection methods, which included medication chart review, patient monitoring until discharge/death, and attending medical rounds. Detected medication errors were intervened with prescribers. Based on the prescribers' decision on delivered interventions, patients were divided into two groups: A (clinical pharmacist's interventions were implemented), and B (clinical pharmacist's interventions were not implemented). We compared patients' outcomes obtained from study groups to evaluate the impact of the implementation of interventions performed by the clinical pharmacist. Results: A total of 271 medication errors (122.62 per 1000 patient hospital-days) were detected among the study patients ( n = 228). Drug–drug interactions (70, 25.8%), guideline nonconformity (51, 18.8%), and inadequate drug monitoring (29, 11%) were the most common types of detected medication errors. Eighty-six percentage of the clinical pharmacist's interventions were implemented by prescribers. Approximately half of medication errors were intercepted before reaching to patients who received the clinical pharmacist's interventions (group A). Overall, medication errors induced 33 preventable ADEs (14.93 per 1000 patient hospital-days), of which the number of preventable ADEs was significantly greater in group B ( P < 0.0001). Significantly in group B, detected medication errors initiated chains of consecutive errors when the clinical pharmacist's interventions were not accepted. Also, this group had significantly increased length of stay ( P < 0.0001), number of deaths ( P = 0.0312), and more than a three-fold greater number of patients intratransferring to higher levels of care ( P = 0.0235; odds ratio, 3.41; 95% confidence interval, 1.08–10.8). Conclusion: The clinical pharmacist-led integrated approach revealed that medication errors commonly occurred among critically ill patients, and the clinical pharmacist's interventions intercepted the majority of these medication errors. The number of preventable ADEs was significantly fewer in a group of patients who received these interventions. However, medication errors formed chains of errors that adversely affected patients' investigated outcomes in the study group with no implementation of the clinical pharmacist interventions.